The p6gag domain of human immunodeficiency virus type 1 is sufficient for the incorporation of Vpr into heterologous viral particles. - Kondo, E (1995)
The vpr gene of human immunodeficiency virus type 1 (HIV-1) encodes a virion-associated regulatory protein. Mutagenesis has shown that the virion association of Vpr requires sequences near the C terminus of the HIV-1 Gag polyprotein Pr55gag. To investigate whether Vpr incorporation is mediated by a specific domain of Pr55gag, we examined the ability of chimeric HIV-1/Moloney murine leukemia virus (MLV) Gag polyproteins to direct the incorporation of Vpr. Vpr expressed in trans did not associate with particles formed by the authentic MLV Gag polyprotein or with particles formed by chimeric Gag polyproteins that had the matrix (MA) or capsid (CA) domain of MLV precisely replaced by the corresponding domain of HIV-1HXB2. By contrast, Vpr was efficiently incorporated upon replacement of the C-terminal nucleocapsid (NC) domain of the MLV Gag polyprotein with HIV-1 p15 sequences. Vpr was also efficiently incorporated into particles formed by a MLV Gag polyprotein that had the HIV-1 p6 domain fused to its C terminus. Furthermore, a deletion analysis revealed that a conserved region near the C terminus of the p6 domain is essential for Vpr incorporation, whereas sequences downstream of the conserved region are dispensable. These results show that a virion association motif for Vpr is located within residues 1 to 46 of p6.